2020
DOI: 10.1021/acs.biomac.0c01520
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Folate-Conjugated Hollow Polymeric Capsules for Accurate Drug Delivery to Cancer Cells

Abstract: This study presents an efficient and systematic approach to synthesize bioapplicable porous hollow polymeric capsules (HPCs). The hydroxyl-functionalized nanoporous polymers with hollow capsular shapes could be generated via the moderate Friedel–Crafts reaction without using any hard or soft template. The numerous primitive hydroxyl groups on these HPCs were further converted to carboxyl groups. Owing to the abundance of highly branched carboxyl groups on the surface of the HPCs, biomolecules [such as folic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 79 publications
1
51
0
Order By: Relevance
“…Then, a brief discussion on their synthetic strategies and functionalization approaches is provided. Subsequently, a detailed description is provided on the applications of POPs in diverse biomedical fields, including drug delivery, 76,101–116 biomacromolecule encapsulation, 117–129 photodynamic and photothermal therapy, 130–147 biosensing, 69,148–151 bioimaging, 152–155 antibacterial, 156–161 bioseparation, 162 and others, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a brief discussion on their synthetic strategies and functionalization approaches is provided. Subsequently, a detailed description is provided on the applications of POPs in diverse biomedical fields, including drug delivery, 76,101–116 biomacromolecule encapsulation, 117–129 photodynamic and photothermal therapy, 130–147 biosensing, 69,148–151 bioimaging, 152–155 antibacterial, 156–161 bioseparation, 162 and others, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biocompatible, fluorescent and targeting agent-conjugated capsules have been presented. It was shown that they permit a more accurate delivery of anticancer drugs and have a better efficacy for drug accumulation [ 27 ]. Similarly, Janus nanoparticles are impressive research materials as they have asymmetric structures and different properties.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, this feature would allow the membrane to capture such metallic species through a coordination bond between triazole rings and cations. This type of membrane is used for numerous applications, such as water purification [ 17 ], antifungal and antimicrobial agents [ 18 , 19 ], CO 2 adsorption [ 20 ], drug encapsulation and release [ 21 ], etc.…”
Section: Introductionmentioning
confidence: 99%